2010
DOI: 10.1038/ijo.2010.88
|View full text |Cite|
|
Sign up to set email alerts
|

Differential effects of high MUFA with high or low P/S ratio (polyunsaturated to saturated fatty acids) on improving hepatic lipolytic enzymes and mediating PPARγ related with lipoprotein lipase and hormone-sensitive lipase of white adipose tissue in diet-induced obese hamster

Abstract: Objective: The aim of this study was to assess the relationship between high monounsaturated fatty acids (MUFAs) with different levels of polyunsaturated-to-saturated fatty acid (P/S) ratios and body fat loss in diet-induced obesity (DIO) models. Design: Male Golden Syrian hamsters were randomly assigned to the control group (n ¼ 12) and obesity group (n ¼ 24) for 4 weeks of the high-fat DIO period; afterward, six hamsters from each group were killed. The remaining control hamsters were still fed a low-fat die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…As carbohydrate stores are depleted, defined mechanisms shift metabolism to reliance on lipid oxidation, with a small degree of protein catabolism, until either a food source is found or the organism enters irreversible terminal cachexia and succumbs. Though the characterization of the three phases was a substantial addition to our understanding of starvation metabolism, there has been substantial work demonstrating that the regulation of substrate utilization goes beyond the hormone-mediated hydrolysis of available substrate [36, 46, 7274]. Lipids exhibit substantial control over metabolism through transcription regulation and through β-oxidation [72, 73, 75, 76], and increase in circulation as a result of food deprivation [9].…”
Section: Substrate Availability and Fuel Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…As carbohydrate stores are depleted, defined mechanisms shift metabolism to reliance on lipid oxidation, with a small degree of protein catabolism, until either a food source is found or the organism enters irreversible terminal cachexia and succumbs. Though the characterization of the three phases was a substantial addition to our understanding of starvation metabolism, there has been substantial work demonstrating that the regulation of substrate utilization goes beyond the hormone-mediated hydrolysis of available substrate [36, 46, 7274]. Lipids exhibit substantial control over metabolism through transcription regulation and through β-oxidation [72, 73, 75, 76], and increase in circulation as a result of food deprivation [9].…”
Section: Substrate Availability and Fuel Metabolismmentioning
confidence: 99%
“…PUFA inhibit sterol regulatory element-binding protein (SREBP) activity via deactivation of hepatic LXR, which impedes lipogenesis [55]. Monounsaturated fatty acids (MUFA) promote lipolysis through inhibition of PPARγ, but do not significantly affect oxidation in rats and hamsters [72, 74]. Saturated fatty acids (SFA) increase low-density lipoprotein (LDL) production, but have also been suggested to contribute to FA chain elongation and to increase the expression of genes involved in hepatic de novo lipogenesis in mice [8183].…”
Section: Substrate Availability and Fuel Metabolismmentioning
confidence: 99%
“…However, when PUFA were added to a high-MUFA diet (high PUFA/SFA ratio) for 8 weeks, the expression and activity of hormone-sensitive lipase (HSL) was upregulated and adipose tissue peroxisome proliferatoractivated gamma (PPARγ) was reduced when compared to a high-MUFA diet, which significantly elevated de novo hepatic lipogenesis (18). Studies comparing the effects of safflower oil (omega 6 FA) versus beef tallow (SFA) in rats reported that the latter group had a higher fat content in the carcass, decreased sympathetic activity and a lower thermogenic effect (19).…”
Section: Dietary Fatty Acids and Body Compositionmentioning
confidence: 99%
“…While SFA play a negative role in body composition, unsaturated fatty acids seem to have the opposite effect through the following mechanisms: decreased energy intake and/or increased energy expenditure through the activation of mitochondrial uncoupling proteins (19); reduced lipid uptake by white adipocytes by suppression of lipoprotein lipase (25); increased lipid catabolism enhancing FA oxidation (β-oxidation) (25); decreased triacylglycerol synthesis through inhibition of enzymes such as fatty acid synthase (FAS) and stearoyl-CoA desaturase-1 (26); decreased expression of transcriptional factors and genes involved in adipose tissue metabolism (18); PPARs are transcriptional factors of the nuclear receptors family, with a key role in controlling lipid metabolism, adipocyte differentiation and lipid storage. There are two important classes of PPARs: PPARα and PPARγ.…”
Section: Dietary Fatty Acids and Body Compositionmentioning
confidence: 99%
“…In metabolic experiments, rats fed saturated fatty acids had higher triacylglycerol, cholesterol, and low-density lipoprotein cholesterol, whereas rats fed unsaturated fatty acids had lower triacylglycerol, cholesterol, and low-density lipoprotein cholesterol as compared with control rats [41, 42]. Moreover, the increased ratio of P/S (polyunsaturated/saturated) fatty acids was beneficial in depleting white adipose tissue accumulation and improved the metabolic status in diet-induced obese hamster [43]. The controlled clinical trials have also indicated that replacing saturated fat with unsaturated fat was more effective in lowering risk of metabolic disorder than simply reducing total fat consumption [44, 45].…”
Section: Discussionmentioning
confidence: 99%